MHD natural convection and entropy generation of ferrofluid in an open trapezoidal cavity partially filled with a porous medium - Astanina, Marina S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2018)
In this study, natural convection combined with entropy generation of Fe3O4-water nanofluid within an open trapezoidal cavity filled with a porous layer and a ferrofluid layer under the effect of uniform inclined magnetic field is numerically analyzed. Porous layer is located on the bottom wall and heated from the left inclined wall. Bottom wall, right and left tilted walls of the cavity are adiabatic except for the active part along the left inclined wall where hot temperature T-h is constant, upper open boundary is kept at constant cold temperature T-c. Governing equations with corresponding boundary conditions formulated in dimensionless stream function and vorticity using Brinkman-extended Darcy model for porous layer have been solved numerically using finite difference method. Numerical analysis has been carried out for a wide range of Hartmann number, magnetic field inclination angle, height of the porous layer and nanoparticles volume fraction. It has been found that an increase in Hartmann number leads to a growth of oscillations amplitude for average Nusselt number and average entropy generation. At the same time inclination angle alpha=pi/2 illustrates unstable behavior of heat and fluid flow. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Uniform inclined magnetic field; Natural convection; Entropy generation; Horizonal porous layer; Open cavity; Ferrofluid; Numerical results